Four new monoterpenoids from an endophytic fungus Periconia sp. F-31. Issue 6 (3rd June 2017) - Liu, Ji-Mei; Zhang, De-Wu; Du, Wen-Yu; Zhang, Min; Zhao, Jin-Lian; Chen, Ri-Dao; Xie, Ke-bo; Dai, Jun-Gui
Abstract: Five monoterpenoids were isolated from the endophytic fungus Periconia sp. F-31, including three new carene-type monoterpenoids, 2-carene-5, 8-diol (1 ), 2-carene-8, 10-diol (2 ), 2-carene-8-acetamide (3 ), one new menthene-type monoterpenoid 8-hydroxy-1, 7-expoxy-2-menthene (4 ), and one known monoterpenoid anethofuran (5 ). The structures of all compounds were elucidated based on a comprehensive spectroscopic data analysis, electronic circular dichroism (ECD), and calculated ECD. Abstract :